2016
DOI: 10.3390/molecules21121748
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins as Emerging Therapeutic Tools in the Treatment of Cholesterol-Associated Vascular and Neurodegenerative Diseases

Abstract: Cardiovascular diseases, like atherosclerosis, and neurodegenerative diseases affecting the central nervous system (CNS) are closely linked to alterations of cholesterol metabolism. Therefore, innovative pharmacological approaches aiming at counteracting cholesterol imbalance display promising therapeutic potential. However, these approaches need to take into account the existence of biological barriers such as intestinal and blood-brain barriers which participate in the organ homeostasis and are major defense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 132 publications
(176 reference statements)
1
65
0
3
Order By: Relevance
“…Oral administration of chitosan/alginate/phospholipid in combination with β‐CD was explored for brain targeting (Shan et al, ). Promising results were shown after clinical trials of KLEPTOSE CRYSMEB and 2‐HP‐β‐CD‐based therapy as cholesterol‐chelating agent in atherosclerosis and Niemann‐Pick type C disease (Coisne et al, ). β‐CD‐based inclusion complexes for targeted drug delivery system incorporating aspirin (Ma et al, ) and diclofenac (Vieira et al, ) have been demonstrated.…”
Section: In Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of chitosan/alginate/phospholipid in combination with β‐CD was explored for brain targeting (Shan et al, ). Promising results were shown after clinical trials of KLEPTOSE CRYSMEB and 2‐HP‐β‐CD‐based therapy as cholesterol‐chelating agent in atherosclerosis and Niemann‐Pick type C disease (Coisne et al, ). β‐CD‐based inclusion complexes for targeted drug delivery system incorporating aspirin (Ma et al, ) and diclofenac (Vieira et al, ) have been demonstrated.…”
Section: In Drug Delivery Systemsmentioning
confidence: 99%
“…Oral administration of chitosan/alginate/phospholipid in combination with β-CD was explored for brain targeting (Shan et al, 2016). Promising results were Clonazepam Me-β-CD Liposomal and microemulsion formulations contain drug-CD complex showed greater solubility and permeation Mura, Bragagni, Mennini, Cirri, and Maestrelli (2014) Curcumin HP-β-CD Increases solubility, transdermal permeation of curcumin, and demonstrated better anti-inflammatory effect Ghanghoria, Kesharwani, Agashe, and Jain (2013) Diclofenac sodium HP-β-CD HP-β-CD grafted polyethyleneimine has proved as a potent skin penetration enhancer with no toxicity or skin irritation Yan et al (2014) Epalrestat ME-β-CD Enhanced dissolution and skin permeation through hairless mouse skin Furuishi et al (2017) Flurbiprofen HP-β-CD Polymeric nanospheres with drug-CD complex showed greater retention of drug in skin as well as stronger anti-inflammatory effect Vega et al (2013) Isotretinoin HP-β-CD Elastic liposomes significantly increased the skin deposition, prolonged drug release and reduce skin irritation Kaur, Puri, and Jain (2010) Itraconazole HP-β-CD Deformable liposomes contain drug-CD complex showed greater cutaneous drug deposition Alomrani, Shazly, Amara, and Badran (2014) Levodopa β-CD Stability of levodopa was enhanced when complexed with β-CD in transdermal patches Obaidat, Al-Shar'i, Tashtoush, and Athamneh (2016) Lornoxicam HP-β-CD Incorporation of CD and propylene glycol in gel improved the skin permeation Al-Suwayeh, Taha, Al-Qahtani, Ahmed, and Badran (2014) Propofol SBE-β-CD Complexation significantly improved the passive and iontophoretic transdermal flux Juluri, Peddikotla, Repka, and Murthy (2013) Terbinafine HP-β-CD Demonstrated the potential of CD as a transungual permeation enhancer Chouhan and Saini (2014) shown after clinical trials of KLEPTOSE CRYSMEB and 2-HP-β-CDbased therapy as cholesterol-chelating agent in atherosclerosis and Niemann-Pick type C disease (Coisne et al, 2016). β-CD-based inclusion complexes for targeted drug delivery system incorporating aspirin (Ma et al, 2015) and diclofenac (Vieira et al, 2016) have been demonstrated.…”
Section: Drug Targetingmentioning
confidence: 99%
“…Recently, various bioactivities of CyDs have been demonstrated, and CyDs have been used as active pharmaceutical ingredients (APIs) against Niemann-Pick disease type C (NPC), [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] leukemia, 77) hyperlipidemia, 78) Alzheimer's disease, [79][80][81][82][83][84] cerebral ischemic injury, 85) atherosclerosis, 86) diabetic kidney disease, 87) chronic renal failure, 88) AIDS, 89,90) influenza, 91) peripheral artery disease, 92) sterility, [93][94][95] solid cancers, [96][97][98][99][100][101] bacterial growth, 102) α-synucleinopathy, 103) GM1-gangliosidosis, 104) septic shock, [105][106][107] hypervitaminosis, 108) and transthyretin-related familial amyloidotic polyneuropathy (FAP) …”
Section: Cyclodextrin-based Supramolecular Pharmacology and Drug Discmentioning
confidence: 99%
“…Several studies have investigated the effect of cholesterol‐reducing agents such as CyDs on neurodegenerative pathologies . Trappsol® [hydroxypropyl‐β‐cyclodextrin (HPBCD)] is currently under clinical trials for the treatment of Niemann–Pick type C (NPC), a lysosomal lipid storage disorder characterized by an accumulation of lipids such as cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effect of cholesterol-reducinga gents such as CyDs on neurodegenerative pathologies. [20,21] Trappsol [hydroxypropyl-b-cyclodextrin (HPBCD)] is Metal dyshomeostasis is central to an umber of disorders that result from, inter alia, oxidative stress,p rotein misfolding, and cholesterol dyshomeostasis. In this respect, metal deficiencies are usually readily corrected by treatment with supplements, whereas metal overload can be overcomeb yt he use of metalselectivechelation therapy.D eferasirox, 4-[(3Z,5E)-3,5-bis(6-oxo-1-cyclohexa-2,4-dienylidene)-1,2,4-triazolidin-1-yl]benzoic acid, Exjade, or ICL670, is used clinically to treat hemosiderosis (iron overload), which often resultsf rom multiple blood transfusions.…”
Section: Introductionmentioning
confidence: 99%